The Interpretation of Foreign Language Inclusions in English Fiction Texts - Ладиненко, Альбіна Павлівна; Ладиненко, А. П.; Ладыненко, Альбина Павловна; Ladynenko, Albina P. (Editura Universitaria Craiova, 2018)
The article is devoted to the types of interpretation of foreign language inclusions (foreignisms) in the English fiction texts written by Ernest Hemingway. Three types of interpretation and identification are presented in the article. The first type suggests that interpretation is made by the author of the text, the second belongs to the editor and the third is connected with active mental work of the reader. Different methods and techniques of all types of interpretation are described in the article in detail and accompanied by the corresponding illustrations. The analysis of Ernest Hemingway’s works showed that the author often integrates the explanation of foreignisms in the main body of the text.

Стаття присвячена різновидам інтерпретації іншомовних включень (іноінізмів) в англомовних художніх текстах Ернеста Хемінгуея. У статті представлено три види тлумачення та ідентифікації. Перший тип передбачає, що інтерпретацію здійснює автор тексту, другий належить редактору, а третій пов'язаний з активною розумовою роботою читача. Різні методи та прийоми всіх видів інтерпретації детально описані в статті та супроводжуються відповідними ілюстраціями. Аналіз творів Ернеста Хемінгуея показав, що автор часто інтегрує пояснення іноземних мов у основну частину тексту.
Ladynenko A. The Interpretation of Foreign Language Inclusions in English Fiction Texts / A. Ladynenko // Analele Universităţii din Craiova. Seria Ştiinţe Filologice. Lingvistică. - № 1-2. - Editura Universitaria Craiova, 2018. - P. 91-105.
Keywords: interpretation; foreignism; fiction text; тлумачення; іноінізм; художній текст; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics